Territorial expansion of the Ragusan commune/Republic and the churches of its patron saints - Marinković, Ana (Array, 2009)
Summary: The churches of St Blaise and the earlier Ragusan patron saints (primarily St Pancras) on the territory of the Ragusan commune/Republic are analysed hagiotopographically from the oldest sources available up to the fifteenth century. Geographical distribution of the church buildings points to two major patterns of topographic expansion and the use of the patron cults in the course of Dubrovnik’s transformation from commune to republic—from a defensive act of marking the borders with temples to a developed system of implanting the state cult into the administrative seats. Such a strategy of spreading the cults of the city patron saints from the implicit demarcation (defence) towards a more symbolic sign of governing (control) reflects a tendency towards a more finely structured Ragusan government